Tradiciones jurídicas y pervivencias oeconomicas en la genealogía constitucional. El caso de Tucumán en 1820 - Zamora, Romina (Pontificia Universidad Católica del Perú. Fondo Editorial, 2019)
The nineteenth-century Spanish-American constitutionalism was inextricably related to the emancipatory process. The constitutional texts sought to establish limits to public powers that were forming in the independent territories, in mined paths of crossroads on which the newest historical and legal studies are elucidating motivations and objectives. From there, it is being discovered that constitutional projects did not ignored a four-hundred-yearold public order, but incorporated elements, subjects and above all, purposes: what is the objective of putting functions and limits to a public power separate from the domestic sphere? Can we trace the survival of an old domestic order —oeconomic— in the constitution, social and political order that should not be confused with the colonial fact? Therefore, it is important to periodize the constitutional journey, since although in the final products, the constitutions that came into force in the nascent Latin American States, the traces of an old mentality are not easily discernible, in the earliest projects they were not only the view but they were determinants in the definition of the subject of law and in the values —catholic, oeconomic— that had to be protected. The nineteenth-century Spanish-American constitutionalism was inextricably related to the preeminent place of the Spanish householder, catholic and land owner. On nineteenth-century Spanish-American constitutionalism, the prescriptive capacity of the catholic economy has weighed, like a sword of Damocles, for the determination of juridical principles.To highlight this hypothesis, it is necessary to perform an almost archaeological tracking of concepts and themes in the first debates on the fundamental law and the resulting texts. For this, we have chosen a provincial constitution, that of the province of Tucumán, written in 1820. Located halfway between the Peruvian space and the River Plate, Tucumán wanted to insert itself in the debate on the formation of the State by dictating its own constitution, as cover letter for a game of powers that was yet to be defined.

El constitucionalismo hispanoamericano del siglo XIX estuvo relacionado inextricablemente con el proceso emancipatorio. Los textos constitucionales que buscaron establecer límites a unos poderes públicos que se estaban formando en los territorios independientes tuvieron trayectorias minadas de encrucijadas. En relación con estos textos, los más nuevos estudios históricos y jurídicos están dilucidando motivaciones y objetivos. A partir de allí, se está descubriendo que los proyectos constitucionales no hicieron tabla rasa sobre un orden público cuatro veces centenario, sino que incorporaron elementos, sujetos y, sobre todo, finalidades: ¿cuál es el objetivo de poner funciones y límites a un poder público separado de la esfera doméstica? O, dicho a la inversa, ¿se puede rastrear la pervivencia de un antiguo orden doméstico —oeconomico— en las cartas magnas, orden social y político que no debe ser confundido con lo colonial? Para eso es importante periodizar el trayecto constitucional, ya que, si bien en los productos finales —las constituciones que entraron en vigencia en los nacientes Estados latinoamericanos— los rastros de una mentalidad antigua no son fácilmente discernibles, en los proyectos más tempranos no solo estuvieron a la vista, sino que fueron determinantes en la definición del sujeto de derecho y en los valores —católicos, oeconomicos—que se debían resguardar. Sobre el constitucionalismo hispanoamericano del siglo XIX ha pesado, como una espada de Damocles para la determinación de principios jurídicos, la capacidad preceptiva de la oeconomia católica.Para arrojar luz sobre esta hipótesis, es necesario realizar un rastreo casi arqueológico de conceptos y temas en los primeros debates sobre la ley fundamental y en los textos resultantes. Para ello, hemos elegido una constitución provincial, la de la provincia de Tucumán, escrita en 1820. Ubicada a mitad de camino entre el espacio altoperuano y el rioplatense, Tucumán quiso insertarse en el debate sobre la formación del Estado dictando su propia constitución, como carta de presentación para un juego de poderes que estaba aún por definirse.
Juridical Traditions and Oeconomic Survival in a Constitutional Genealogy. The Case of Tucumán in 1820
Keywords: Oeconomia; Economía política; Sujeto de derecho; Padre de familia; Vecino-ciudadano; https://purl.org/pe-repo/ocde/ford#5.05.00